Renal safety of Hydroxyethyl starch 130/0.42 after cardiac surgery: a retrospective cohort analysis - Morath, Benedict; Meid, Andreas; Rickmann, Johannes; Soethoff, Jasmin; Verch, Markus; Karck, Matthias; Zaradzki, Marcin (Drug safety, 2021)
Introduction  The risk for renal complications from hydroxyethyl starch 130/0.42 (HES) impacts treatment decisions in patients after cardiac surgery. - Objective  The objective of this study was to determine the impact of postoperatively administered HES on renal function and 90-day mortality compared to sole crystalloid administration in patients after elective cardiac surgery. - Methods  Using electronic health records from a university hospital, confounding-adjusted models analyzed the associations between postoperative HES administration and the occurrence of postoperative acute kidney injury. In addition, 90-day mortality was evaluated. The impact of HES dosage and timing on renal function on trajectories of estimated glomerular filtration rates over the postoperative period was investigated using linear mixed-effects models. - Results  Overall 1009 patients (45.0%) experienced acute kidney injury. Less acute kidney injury occurred in patients receiving HES compared with patients receiving only crystalloids for fluid resuscitation (43.7% vs 51.2%, p = 0.008). In multivariate acute kidney injury models, HES had a protective association (odds ratio: 0.89; 95% confidence interval 0.82-0.96). Crystalloids were not as protective as HES (odds ratio: 0.98; 95% confidence interval 0.95-1.00). There was no association between HES and 90-day mortality (odds ratio: 1.05; 95% confidence interval 0.88-1.25). Renal function trajectories were dose dependent and biphasic, HES appeared to slow down the late postoperative decline. - Conclusions  This study showed no association between HES and the postoperative occurrence of acute kidney injury and thus further closes the evidence gap on HES safety in cardiac surgery patients. Although this was a retrospective cohort study, the results indicated that HES might be safely administered to cardiac surgery patients with regard to renal outcomes, especially if it was administered early and dosed appropriately.
Gesehen am 04.09.2023